Translating popular proverbs between faithfulness and unfaithfulness - Adlani, Amel (Journal of Human Sciences, 2023)
Popular proverbs translation ask many problems in the field of translation. This translation is very often confronted by many linguistic and cultural barriers mainly concerning the transfer of their semantic and poetic specifities in the Target language, the fact that calls the element of « Faithfulness » into question. In the present paper, we will try to highlight the different problems that face the translator during the ranslation of popular proverbs, we will also discuss the translaion startegies adopted in their translation from the source language into the target on that can realise the notion of faithfulness.